2022
DOI: 10.3390/foods11121673
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Wild and Farmed Sea Bass by Using New Spectrometry and Spectroscopy Methods

Abstract: European sea bass (Dicentrarchus labrax L.) is one of the most economically important fish species in the Mediterranean Sea area. Despite strict requirements regarding indications of production method (wild/farmed), incorrect labelling of sea bass is a practice still frequently detected. The aim of this study was to evaluate the capabilities of two techniques, Near-InfraRed (NIR) spectroscopy and mass spectrometry, to discriminate sea bass according to the production method. Two categories were discriminated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…All the cited methods are known to be time-consuming and destructive, often not suitable in the context of field analysis. Therefore, non-destructive, cheap, and rapid techniques, such as near-infrared (NIR) spectroscopy, have also been recently applied [3][4][5][6][7]. However, the use of omics techniques is certainly useful for deeper characterization of fish freshness since it is characterized by complex processes that can be influenced by several endogenous (e.g., spoilage) and exogenous (e.g., undeclared freezing/thawing treatment, adulteration with illicit additives, etc.…”
Section: Of 25mentioning
confidence: 99%
See 2 more Smart Citations
“…All the cited methods are known to be time-consuming and destructive, often not suitable in the context of field analysis. Therefore, non-destructive, cheap, and rapid techniques, such as near-infrared (NIR) spectroscopy, have also been recently applied [3][4][5][6][7]. However, the use of omics techniques is certainly useful for deeper characterization of fish freshness since it is characterized by complex processes that can be influenced by several endogenous (e.g., spoilage) and exogenous (e.g., undeclared freezing/thawing treatment, adulteration with illicit additives, etc.…”
Section: Of 25mentioning
confidence: 99%
“…Consequently, while some interesting applications of both omics and spectroscopy have been reported to differentiate the most common frozen/thawed fish frauds [8][9][10][11], novel methods to unveil other illicit field practices based on the misuse of additives that are known to prevent and/or delay fish spoilage are still limited [4] and therefore needed.…”
Section: Of 25mentioning
confidence: 99%
See 1 more Smart Citation
“…( Risoluti et al, 2015 ; Pennisi et al, 2021 ; Cavallini et al, 2022 ). Handheld NIR spectroscopy was proposed as discrimination tool between wild and farmed sea bass by ( Esposito et al, 2022 ). Yakes et al (2021) reported the analysis of two fish species and compared the performance of handheld NIR devices.…”
Section: Applications To Food Quality Characterization and Adulterationsmentioning
confidence: 99%
“…Chromatographic techniques combined with different mass spectrometry (MS) technologies [ 9 ], including time of flight spectrometry (TOF), high-resolution mass spectrometry (HRMS) and isotope ratio mass spectrometry (IRMS) [ 10 ], have been used extensively for food traceability and authentication, particularly for honey, wine, fish, coffee and rice [ 11 , 12 , 13 ].…”
mentioning
confidence: 99%